FORMATION OF STUDENTS' LEGAL OUTLOOK AS A SOCIO-PEDAGOGICAL PROBLEM - Usmonov, Zafar (Журнал иностранных языков и лингвистики, 2023)
As we know from life experience, it is effective to hold legal educational events for the formation of legal consciousness, legal culture, and legal outlook in society. For this, it is necessary to constantly hold events aimed at explaining the history of our people and national